Financial Sector Assessment : Tunisia - World Bank (Washington, DC, 2013)
The joint International Monetary Fund/World Bank mission that visited Tunis from January 16 - 31 and March 27 - 31, 2006 as part of the Financial Sector Assessment Program (FSAP) update for Tunisia carried out a detailed analysis of the ability of the Tunisian banking sector to support the country's development objectives. Upon invitation of the Governor of the Central Bank of Tunisia (BCT), the mission organized three well attended workshops on: (i) the restructuring of nonperforming loans; (ii) management of public banks; and (iii) the use of information for financing Small Medium Enterprises (SMEs) and individuals. The Tunisian economy registered a strong performance over the past decade. With average real growth rates of 5 percent since 2000, real per capita income increased by 20 percent in a context of macroeconomic stability. In 2005, the rate of inflation declined to 2 percent and the fiscal deficit was brought down to around 3 percent. The current account deficit on the balance of payments narrowed considerably since 2000, to reach 1.3 percent of Gross domestic product (GDP) in 2005 in spite of further progress in trade liberalization.